Gods, Guns, and Globalization: Religious Radicalism and International Political Economy - Bahramitash, Roksana; Biswas, Shampa; Buss, Doris E.; Denemark, Robert A.; Denemark, Robert A.; Dillman, Bradford; Frank, Adam; Gallaher, Carolyn; Maloney, Suzanne; Pasha, Mustapha Kamal; Reuveny, Rafael; Tétreault, Mary Ann; et al. (International Political Economy Yearbook, 2022)
Is it accurate to equate "fundamentalism" with antimodernism? What explains the growing importance of religious activists in world politics? Guns, Gods, and Globalization explores the multifaceted phenomenon of religious resurgence, ranging from the Christian right in the U.S. to ethnonationalist movements across North Africa and Asia. The authors' focus on the complex relationship between religious revivalism and globalization results in a nuanced study of religious political movements as they emerge in the context of rapid socioeconomic change